The disabled sporting body and the media - Erhart, Itır (Akdeniz İletişim, 2012)
ABSTRACT: After discussing the philosophical concept of othering this study will focus on the depiction of a “minority group”, namely, disabled athletes in Turkish sports media, i.e., sports pages of mainstream Turkish print media and Turkish sport newspapers. It will be argued that the discourse used by the media leads to the identification of the disabled athletes as the other — as opposed to the “normal”, “able-bodied” athletes. The analysis will focus on the depiction of disabled athletes either as inspirational figures, romantic heroes who transcend their limits, or as tragic heroes who inspire fear and pity, or even sometimes as one of the elements which add color to competitions. It will also discuss how the shock which occurs when expectations based on these stereotypes are not met is depicted in sports media, i.e., when disabled athletes get involved in a fight or a doping scandal. The use of problematic terms such as “against her normal rivals”, “even disabled athletes”, “a pleasant sight”, and “overcoming obstacles” will also be discussed. Four mainstream newspapers (Akşam, Zaman, Radikal, Hürriyet) and one sport newspaper (Fanatik) will be utilized for this analysis. The ethical problems with the coverage of disabled athletes will also be examined.

ÖZET: Bu makalede basındaki söylemin engelli sporculara yönelik önyargıları tetiklediği ve onları ötekileştirdiği iddiasından yola çıkıldı. Bu bağlamda, 2005-2008 yılları arasında Fanatik, Akşam, Zaman, Radikal ve Hürriyet gazetelerinde engelli sporcularla ilgili çıkan haberlerin analizi yapıldı. Haber dili ve kullanılan fotoğraflar irdelendi. Türk basınında karşımıza çıkan üç engelli sporcu stereotipine -engelleri aşan, mucizeler yaratan romantik kahramanlar, insani rekabet arındırılmış, bizde acıma ve korku duygularını uyandıran, göz yaşartıcı hikayelerin kahramanları ve müsabakalara renk ya da hoş bir görüntü katan unsurlar- dikkat çekilip, bu stereotipler etik açıdan değerlendirildi.
Engelli sporcu bedenler ve medya
Keywords: Sports; Disability; Turkish Sports Media; Medical Model; Social Model; Disabled Sports; Türk Spor Basını; Engellilik; Medikal Model; Sosyal Model; Engelli Sporcular